PENDIDIKAN KARAKTER ANAK DENGAN METODE WHOLE BRAIN TEACHING DALAM PEMBELAJARAN DI BIMBINGAN BELAJAR PENCIL GENERATION DI LINGKUNGAN V SIMALINGKAR B MEDAN TUNTUNGAN - Juli Loisiana Butar-butar; Ferdinand Sinuhaji; Jenita Anjani Br. Sembiring (LPPM UMRI, 2019)
The environment greatly influences the establishment of human character and large urban suburbs are areas inhabited majority by the lower middle class. The main goal in community service is to provide character education through free tutoring for Mathematics and English for primary school in course center Pencil Generation in Zone V Simalingkar B Sub-District Medan Tuntungan North Sumatera. The method used in process of the character education is the Whole Brain Teaching (WBT) method which is integrated during the teaching and learning process in the course center. The steps taken by the team in order to carry out this activity are as follows: (1). preparation for service activities, (2). provide guidance about characters, (3). forming learning groups based on class, (4). guide children to learn with the Whole Brain Teaching method, (5). sometimes play games related to Mathematics and English. The result of this service is academic improvement in Mathematics and English. Beside the academic improvement, there is also an increase in character that is manners, perseverance, discipline, tolerance, and caring.